Nondestructive testing of composite T-Joints by TNDT and other methods; Polymer Testing; Vol. 94 - Vavilov V. P. Vladimir Platonovich; Chulkov A. O. Arseniy Olegovich; Dubinsky S. V. Stanislav Vyacheslavovich; Burleigh D. D. Douglas; Shpilnoy V. Yu. Viktor Yurjevich; Derusova D. A. Dariya Aleksandrovna; Zhvyrblya V. Yu. Vadim Yurievich (2021, 2021)
Title screen